Implementasi Sistem Informasi Dinas Pariwisata Kabupaten Enrekang Berbasis Cloud Computing - Mirsal Wahyudi; Mahiruddin; Andi Irfan (Jurnal Manajemen Informatika, Sistem Informasi dan Teknologi Komputer (JUMISTIK), 2022)
The rapid development of information technology provides its own challenges for the tourism office of the Enrekang district in dealing with the current situation. Where the problem found is that not many people know about the various tourist attractions in Enrekang Regency, so that there is a lack of tourists visiting Enrekang Regency, we need a system that is able to provide tourism information digitally. To achieve this, an information system was created with the implementation of cloud computing with the type of service used Platform as a Service (PaaS) which can provide convenience in managing and facilitating the delivery of information. One alternative to overcome this is Cloud Computing. Cloud Computing is a service that allows users to access electronically by utilizing the internet network to create one very large computer and save resources and hardware used. Cloud Computing has also provided data security guarantees so that users do not have to worry about data loss or damage to stored data.